IMPLEMENTASI MEDIA PUZZLE KATA DALAM PEMBELAJARAN TEKS NARASI UNTUK MENINGKATKAN KEMAMPUAN MEMBACA SISWA KELAS IVC SD 002 SAROLANGUN - Saskia, Arna; Thoyib, Hadi; Sari, Albi Permata; Widiawati; Widya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This qualitative descriptive study focuses on evaluating the implementation of Media Puzzle Kata as a pedagogical intervention to optimize students' reading comprehension skills in narrative text learning. The study was conducted on subjects in Class IV C of SD Negeri 002/VII Pasar Sarolangun II. Data collection was carried out through a combination of participatory observation triangulation, in-depth interviews, and questionnaires, which were then analyzed using data reduction and source triangulation validation. The results of the study show that the use of Media Puzzle Kata has proven to have a significant and effective positive impact. This media has succeeded in changing the classroom atmosphere from passive to more dynamic, active, and enjoyable, thereby overcoming the problem of low learning motivation. Through puzzle-building activities, students not only gained a strong understanding of sentence structure and vocabulary but also improved their ability to interpret story content, identify narrative elements, and build confidence in reading. In conclusion, word puzzles are a relevant and efficient learning strategy for improving literacy and collaboration at the elementary school level.